PENGARUH PELATIHAN DAN PENGALAMAN KERJA TERHADAP KINERJA PEGAWAI (Studi pada Kantor Badan Pusat Statistik di Maluku) - Senda Yunita Leatemia (Manis: Jurnal Manajemen dan Bisnis, 2018)
Senda Yunita Leatemia, this study aimed to determine the effect of training andwork experience to the performance of employees in Badan Pusat StatistikMaluku. This type of research used in this study is quantitative and researchmethods used is the method of explanation (explanatory research). In this studyused all population as sample and obtained 61 valid sample. The analyticalmethod used is multiple linear regression analysis to test the hypothesis. Theresults of this study prove two things, there is a simultaneous effect betweentraining and work experience of the performance and there is a partial effect workexperience on the performance, while training has no effect on the performance.This means that work experience can significantly improve the performance ofemployees who worked at the Badan Pusat Statistik Maluku.